Edukasi Kesehatan Gizi dan Deteksi Sederhana Yodium: Strategi Preventif Gangguan Akibat Kekurangan Yodium (GAKY) di Kalangan Siswa MA Asshodiqiyah - Lestari, Asih Puji; Kusumawati, Dwi Endah; Fawaid, Ainun; Haekal, Ghulam; Agustin, Stevi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Iodine Deficiency Disorders (IDD) remain a serious threat to the health and cognitive development of adolescents. This community service activity aims to improve nutritional health literacy and practical skills among students of MA Asshodiqiyah Semarang in detecting iodine content in salt. The implementation method included interactive education, evaluation through pre-tests and post-tests, and hands-on practice of simple iodine testing. The program was conducted in December 2025 and involved 15 tenth-grade students at MA Asshodiqiyah. The results showed a significant increase in student understanding, with average knowledge scores rising from 58 (pre-intervention) to 86 (post-intervention). The skills evaluation further revealed that 85% of students were able to perform iodine testing independently and correctly. The combination of theoretical education and direct practice proved effective in raising students' critical awareness of the quality of salt they consume. This activity is expected to serve as a sustainable preventive strategy to combat IDD within school and pesantren (Islamic boarding school) environments.